The structure of HLA-DR52c: Comparison to other HLA-DRB3 alleles - Dai, Shaodong (National Academy of Sciences, 2008)
Class II major histocompatibility complex (MHCII) molecules present antigens to CD4(+) T cells. In addition to the most commonly studied human MHCII isotype, HLA-DR, whose β chain is encoded by the HLA-DRB1 locus, several other isotypes that use the same α chain but have β chains encoded by other genes. These other DR molecules also are expressed in antigen-presenting cells and are known to participate in peptide presentation to T cells and to be recognized as alloantigens by other T cells. Like some of the HLA-DRB1 alleles, several of these alternate DR molecules have been associated with specific autoimmune diseases and T cell hypersensitivity. Here we present the structure of an HLA-DR molecule (DR52c) containing one of these alternate β chains (HLA-DRB3*0301) bound to a self-peptide derived from the Tu elongation factor. The molecule shares structurally conserved elements with other MHC class II molecules but has some unique features in the peptide-binding groove. Comparison of the three major HLA-DBR3 alleles (DR52a, b, and c) suggests that they were derived from one another by recombination events that scrambled the four major peptide-binding pockets at peptide positions 1, 4, 6, and 9 but left virtually no polymorphisms elsewhere in the molecules.